Analisis Buku Ajar Bahasa Arab Berdasarkan Prinsip (Studi Analisis Buku Bahasa Arab kelas 8 pada semester 1) - Alfi Nurrosyiid; Nurselafia; Muhammad Tareh Aziz (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2022)
Books have an important role in teaching and learning activities and the development of knowledge. The MTS grade 8 Arabic textbook published by the Indonesian Ministry of Religion, which should have been thoroughly researched before being published, is alleged to contain several errors. Therefore, this analysis needs to be done to correct and evaluate errors in writing Arabic textbooks. This study uses a qualitative approach to library research or what is called library research. In this analysis the researcher uses content analysis data collection techniques or what is often called